2009
DOI: 10.3998/ark.5550190.0010.a26
|View full text |Cite
|
Sign up to set email alerts
|

Solvent-free synthesis of some N4O2, N4S2 and N6 Schiff-base ligands assisted by microwave irradiation

Abstract: A microwave-assisted solvent-free condensation of various aldehydes with two different piperazine-based amines efficiently afforded a series of bis-imine ligands in high yields. All products were characterized by their melting point, elemental analysis, IR, EI mass, 1 H and 13 C NMR spectra. This method is fast, involves no solvent and has easy work-up and high yields of the desired products.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 19 publications
0
5
0
Order By: Relevance
“…1 H NMR (400 MHz, CDCl 3 , ppm) δH: 1.81 (m, 4H, 9-H), 2.33−2.40 (m, 12H, 10-H, and 11-H), 3.58 (t, 3 J = 8.0 Hz, 4H, 8-H), 6.79−7.31 (m, 6H, aromatic ring), 8.20 (s, 2H, 7-H, CN), 13.49 (bs, 2H, OH). 13 C NMR (400 MHz, CDCl 3 , ppm) δC: 27.8 (t, C-9), 53.2 (t, C-11), 55.8 (t, C-10), 57.4 (t, C-8), 109.8 (s, C-6), 119.1 (d, C-5), 120.1 (s, C-2), 153.2, 154.8 (d, C-3 or C-4), 160.5 (s, C-5) (aromatic ring), 163.8 (d, C-7, CN) . Scheme shows the structure of the synthesized Schiff base.…”
Section: Methodsmentioning
confidence: 99%
“…1 H NMR (400 MHz, CDCl 3 , ppm) δH: 1.81 (m, 4H, 9-H), 2.33−2.40 (m, 12H, 10-H, and 11-H), 3.58 (t, 3 J = 8.0 Hz, 4H, 8-H), 6.79−7.31 (m, 6H, aromatic ring), 8.20 (s, 2H, 7-H, CN), 13.49 (bs, 2H, OH). 13 C NMR (400 MHz, CDCl 3 , ppm) δC: 27.8 (t, C-9), 53.2 (t, C-11), 55.8 (t, C-10), 57.4 (t, C-8), 109.8 (s, C-6), 119.1 (d, C-5), 120.1 (s, C-2), 153.2, 154.8 (d, C-3 or C-4), 160.5 (s, C-5) (aromatic ring), 163.8 (d, C-7, CN) . Scheme shows the structure of the synthesized Schiff base.…”
Section: Methodsmentioning
confidence: 99%
“…However, it has rarely been used in the synthesis of imines. N -Alkyl or N -aryl imines have been prepared by microwave irradiation in the absence of a catalyst or in the presence of calcium oxide, silica gel, or the solid acid montmorillonite K-10 or a ZrO 2 /S 2 O 8 2– solid superacid as a catalyst.…”
Section: Introductionmentioning
confidence: 99%
“…An Agilent Technologies® 5975C spectrometer was then used to scan the mass spectra according to the estimated index (EI)method at 70 eV. The 1 H and 13 C NMR spectra of the compounds were scanned using a Bruker® 500 MHz spectrometer. Tetramethylsilane (TMS) was utilised as a reference for internal standards.…”
Section: Instrumentation and Spectral Measurementsmentioning
confidence: 99%
“…The 1 HNMR spectrum of H2L2 (Figure 3) displayed the same signals with the absence of the CH=C signal due to the chloride atom. The 13 CNMR spectrum of the two ligands indicated that the signal for C=N was between 194.9 to 198ppm and C-OH at 159.38 to 158.5 ppm for H2L1 and H2L2, respectively. Signals for the other carbon atoms were also noted.…”
Section: Characterization Of Ligands and Complexesmentioning
confidence: 99%
See 1 more Smart Citation